2014
DOI: 10.1590/1983-084x/12_113
|View full text |Cite
|
Sign up to set email alerts
|

Influência de diferentes extratos aquosos de plantas medicinais no desenvolvimento de Colletotrichum gloeosporioides e de Fusarium moniliforme

Abstract: 5, 10 and 20% (w:v) and incorporated into the PDA (potato dextrose agar) culture medium before sterilization by autoclaving. Later, an 8 mm diameter disc of each pathogen mycelium was transferred to the center of the Petri dishes. After 24, 48 and 96 hours of incubation in a growth chamber at 22 ± 2 °C and a photoperiod of 12 hours, we evaluated the mycelial growth of F. moniliforme, and C. gloesporioides. In the last period of incubation, we quantified the production of conidia of each fungus. For the germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…A study developed by Silva and coworkers (2014), with the 20% extract and paper disc method, ie without autoclaving, indicated a 17.04% inhibition of this fungus. The infusion of lemongrass leaves in PDA medium (autoclaved) led to a median inhibition, being higher at a concentration of 20% when compared to previously reported 5 and 10% (Marcondes et al, 2014). Using the same methodology as in the present study, Rozwalka et al (2008) observed a 26.66% inhibition of Cg growth, isolated from guava.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…A study developed by Silva and coworkers (2014), with the 20% extract and paper disc method, ie without autoclaving, indicated a 17.04% inhibition of this fungus. The infusion of lemongrass leaves in PDA medium (autoclaved) led to a median inhibition, being higher at a concentration of 20% when compared to previously reported 5 and 10% (Marcondes et al, 2014). Using the same methodology as in the present study, Rozwalka et al (2008) observed a 26.66% inhibition of Cg growth, isolated from guava.…”
Section: Resultssupporting
confidence: 66%
“…The autoclaved extract in question was a good inhibitor of Fox growth (63.75%). No information on antagonistic sage extract was accessed for Fox in the literature; however, against F. solani, median inhibition was observed (Marcondes et al, 2014). The aqueous extract obtained by 50% hot water infusion was not effective in inhibiting Ss (Pansera et al, 2012), as observed in the present study.…”
Section: Resultsmentioning
confidence: 43%
See 2 more Smart Citations
“…Brito and Nascimento (2015) obtained similar results when they studied plant extract fungitoxic potential on Curvularia eragrostidis and observed that garlic, ginger, neem and citronela, starting at 25% concentration, presented bigger plant toxic effects in the in vitro analysis; reducing mycelial growth and sporulation as well as fungus germination. Marcondes et al (2014) also observed that 20% garlic extract completely inhibited C. gloeosporioidese conidia germination and reduced the number and germination of Fusarium moniliforme conidia.…”
Section: Plant Extract Effect On C Gloeosporioides Conidia Germinationmentioning
confidence: 76%